The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mus.25106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and insulin-like growth factor-1 on rat neurotrophin receptor expression after nerve injury

Abstract: Local IGF-1 treatment reverses age-related declines in recovery after peripheral nerve injuries by suppressing p75(NTR) upregulation and pro-apoptotic complexes. IGF-1 may be considered a viable adjuvant therapy to current treatment modalities. Muscle Nerve 54: 769-775, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The mean age in our study was 10 years, in contrast to 30 years in the report by Guelinckx and 46 years in the adult report by Terzis and Karypidis. The literature supports that axonal regeneration is poorer with increasing age, 44,46 and this is likely to be the principal cause for the difference. Currently, we choose to limit this procedure as a rule of thumb to patients younger than 30 years.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mean age in our study was 10 years, in contrast to 30 years in the report by Guelinckx and 46 years in the adult report by Terzis and Karypidis. The literature supports that axonal regeneration is poorer with increasing age, 44,46 and this is likely to be the principal cause for the difference. Currently, we choose to limit this procedure as a rule of thumb to patients younger than 30 years.…”
Section: Discussionmentioning
confidence: 93%
“…The second technical difference is the choice of how the platysma muscle is innervated. It is clear that direct neurotization can lead to de novo formation of neuromuscular junctions; however, studies have shown this to be inferior to reinnervation through neurorrhaphy, 44 except in situations of prolonged denervation. 41,42,45 By introducing a vascularized muscle, the nerve to the platysma can be raised with the flap and superior reinnervation of the muscle can be expected through a direct neurorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
“…Mini-osmotic pumps provide a sustained, local delivery of exogenous IGF-1 ( Table 5 ; Kanje et al, 1989 ; Sjoberg and Kanje, 1989 ; Ishii and Lupien, 1995 ; Tiangco et al, 2001 ; Fansa et al, 2002 ; Apel et al, 2010 ; Luo et al, 2016 ). This technique involves subcutaneous implantation of an osmotic pump in the abdomen with extension of a catheter from the pump to the transected nerve site.…”
Section: Delivery Of Exogenous Igf-1mentioning
confidence: 99%
“…Yet, reduced physical activity seen during elderly may alter brain activation, impairing motor status and increasing motor deficits (Godde and Voelcker-Rehage, 2017 ). Functional deficits may be the consequence of a loss of nerve fibers (Knox et al, 1989 ; Hashizume and Kanda, 1995 ; Ugrenovic et al, 2016 ), myelin sheath abnormalities (Ceballos et al, 1999 ), changes in extracellular matrix (Esquisatto et al, 2014 ), as well as changes in neuronal or glial expression of membrane channels, neurotrophic factors, and cell adhesion molecules, thereby decreasing axoplasmic transport (Milde et al, 2015 ; Krishman et al, 2016 ; Luo et al, 2016 ; Moldovan et al, 2016 ; Takagishi et al, 2016 ). Although many mechanisms seeking explanations for functional deficits have already been suggested, it is not known whether the weight-bearing capacity of Wistar rats declines with advancing age.…”
Section: Introductionmentioning
confidence: 99%